Accumulation of the Major Components from Polygoni Multiflori Radix in Liver and Kidney after Its Long-Term Oral Administrations in Rats - Li, Dan; Lyu, Yuanfeng; Zhao, Jiajia; Ji, Xiaoyu; Zhang, Yufeng; Zuo, Zhong (Planta Medica, 2021)
Although Polygoni Multiflori Radix (PMR) has been widely used as a tonic and an anti-aging remedy for centuries, the extensively reported hepatotoxicity and potential kidney toxicity hindered its safe use in clinical practice. To better understand its toxicokinetics, the current study was proposed, aiming to evaluate the biodistributions of the major PMR components including 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside (TSG), emodin, emodin-8-O-β-D-glucopyranoside (EMG) and physcion as well as their corresponding glucuronides following bolus and multiple oral administrations of PMR to rats. Male Sprague-Dawley rats received a bolus dose or 21 days of oral administrations of PMR concentrated granules at 4.12 g/kg (equivalent to 20.6 g/kg raw material). Fifteen minutes after bolus dose or the last dose on day 21, rats were sacrificed and the blood, liver, and kidney were collected for the concentration determination of both parent form and glucuronides of TSG, emodin, EMG, and physcion by HPLC-MS/MS. Among all the tested analytes, TSG, EMG, EMG glucuronides in liver and TSG, EMG, as well as all the glucuronides of these analytes in the kidney demonstrated the most significant accumulation after multiple doses. Moreover, the levels of the parent analytes were all significantly higher in liver and kidney in comparison to their plasma levels. Strong tissue binding of all four analytes and accumulation of TSG, EMG, and EMG glucuronides in the liver and TSG, EMG, as well as the glucuronides of all four analytes in the kidney after multiple dosing of PMR were considered to be associated with its toxicity.
Keywords: Polygoni Multiflori Radix; Polygonum multiflorum Thunb.; 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside; emodin; emodin-8-O-β-D-glucopyranoside; physcion; liver and kidney distribution